The Quality/Safety Medical Index: Implementation and Analysis. - Reiner, Bruce (Journal of Digital Imaging, 2015)
Medical analytics relating to quality and safety measures have become particularly timely and of high importance in contemporary medical practice. In medical imaging, the dynamic relationship between medical imaging quality and radiation safety creates challenges in quantifying quality or safety independently. By creating a standardized measurement which simultaneously accounts for quality and safety measures (i.e., quality safety index), one can in theory create a standardized method for combined quality and safety analysis, which in turn can be analyzed in the context of individual patient, exam, and clinical profiles. The derived index measures can be entered into a centralized database, which in turn can be used for comparative performance of individual and institutional service providers. In addition, data analytics can be used to create customizable educational resources for providers and patients, clinical decision support tools, technology performance analysis, and clinical/economic outcomes research.